PRELIMINARY ANALYSIS OF THE REQUIREMENTS FOR FUSION FROM WITHIN AND FUSION FROM WITHOUT BY NEWCASTLE DISEASE VIRUS - Bratt, Michael A. (1969)
Different strains of Newcastle disease virus vary in their ability to induce cell fusion. When administered to cells at high multiplicities of infection some strains induce cell fusion within three hours. This type of fusion is apparently caused by the virus particles in the inoculum, since it can be induced by noninfectious virus and does not require protein synthesis for induction. It has been designated fusion from without (FFWO). Other strains induce fusion mainly at low multiplicities of infection. This fusion is induced only by infectious virus, and requires protein synthesis for induction. Probably included among these required proteins is a viral antigen which must be available at the cell surface in order for fusion to occur. This type of fusion has been designated fusion from within (FFWI).